2017
DOI: 10.1038/s41598-017-18180-6
|View full text |Cite
|
Sign up to set email alerts
|

Coinfection takes its toll: Sea lice override the protective effects of vaccination against a bacterial pathogen in Atlantic salmon

Abstract: Vaccination is considered crucial for disease prevention and fish health in the global salmon farming industry. Nevertheless, some aspects, such as the efficacy of vaccines, can be largely circumvented during natural coinfections. Sea lice are ectoparasitic copepods that can occur with a high prevalence in the field, are frequently found in co-infection with other pathogens, and are highly detrimental to fish health. The aim of this case-control study was to evaluate the interaction between the detrimental eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 53 publications
1
42
0
Order By: Relevance
“…These authors demonstrated that the vaccinated Nile tilapia experimentally parasitized with T. heterodentata, G. cichlidarum and I. multifiliis showed lower relative protection survival (RPS) than vaccinated fish without further parasitic infection. This finding is similar to what has been reported in Atlantic salmon, Salmo salar , where sea louse, Caligus rogercresseyi , may explain the reduced efficacy of vaccines against the bacterial pathogen, Piscirickettsia salmonis , in salmon sea cages (Figueroa et al, 2017).…”
Section: The Co‐infections In Tilapia: Types and Effectssupporting
confidence: 89%
See 1 more Smart Citation
“…These authors demonstrated that the vaccinated Nile tilapia experimentally parasitized with T. heterodentata, G. cichlidarum and I. multifiliis showed lower relative protection survival (RPS) than vaccinated fish without further parasitic infection. This finding is similar to what has been reported in Atlantic salmon, Salmo salar , where sea louse, Caligus rogercresseyi , may explain the reduced efficacy of vaccines against the bacterial pathogen, Piscirickettsia salmonis , in salmon sea cages (Figueroa et al, 2017).…”
Section: The Co‐infections In Tilapia: Types and Effectssupporting
confidence: 89%
“…Moreover, immunosuppression can cause vaccines to lose their protectiveness (Figueroa et al, 2017; Martins et al, 2011). For example, it has been demonstrated tilapias vaccinated against S. iniae and parasitized with several ectoparasites such as Trichodina , Gyrodactylus and I. multifiliis showed lower relative percentage survival (RPS) in comparison with vaccinated and parasite‐free fish (Martins et al, 2011).…”
Section: Mechanisms Of Synergistic Co‐infectionsmentioning
confidence: 99%
“…It would be recommended that diagnostic approaches for fish pathologists routinely include screening for both bacterial and viral pathogens. Vaccination may be option to potentially mitigate the severity of co‐infection, although it has been recently reported that parasitic co‐infections may compromise vaccine efficacy for some bacterial pathogens (Figueroa et al, ). Further experimentation and documentation of the incidence and impact of co‐infections in fish would be important aid in the development of new strategies for disease control or prevention.…”
Section: Discussionmentioning
confidence: 99%
“…Of course, there will be implications for diagnosis and immunoprophylaxis (Kotob et al 2016). In particular, it has been considered to be highly likely that co-infection may well reduce the beneficial effect of vaccination (Figueroa et al 2017). Examples of co-infection have reached the scientific literature, and incidences appear to be increasing possibly as scientists become aware of, and actively look for, evidence.…”
Section: The Issue Of Possible Co-infectionsmentioning
confidence: 99%